Comparison of Serum Zinc and Copper Level in Psoriatic and Non-Psoriatic Individual (Bangladesh Medical Journal, 2022)
Psoriasis is a common chronic inflammatory disease of skin and multiple organs of body. The exact etiology of psoriasis is not yet certain. It is assumed that trace elements may have some role in pathogenesis of psoriasis. They can act as co-enzymes for metabolism and can act as antioxidants against free radicals. Therefore they can participate in epidermal proliferation and inflammatory process of psoriasis. This study aimed to evaluate the relation between psoriasis and trace elements namely zinc and copper. This study was conducted on 40 diagnosed cases of psoriasis and 40 non psoriatic individuals in the department of Dermatology and Venereology in Bangabandhu Sheikh Mujib Medical University, Dhaka. Biochemical analyses of serum copper and zinc were analyzed and compared statistically with cases and healthy controls. Serum zinc level was significantly lower and serum copper level was significantly higher in patient with psoriasis compared to control (p= < 0.001). Individuals with moderate to severe psoriasis had significantly lower zinc levels and significantly higher copper levels than patients with mild psoriasis, according to Psoriasis area and Severity Index Score (p= < 0.05). Correction of serum zinc and copper level could be beneficial for psoriasis patients.Bangladesh Med J. 2021 May; 50(2) : 28-31